Recoveries from financial crises: The United States and Argentina in the 1890s - Peter Bent (Essays in Economic & Business History (EEBH), 2021)
The United States and Argentina both experienced severe financial crises in the early 1890s. The causes of these crises have been studied in depth. Here, I analyze the recoveries from these crises, comparing the factors that propelled or hindered renewed economic growth, focusing on how changes in commodity prices and trade policies impacted post-crisis economic activity. Sustained recovery only occurred in the United States when wheat prices surged in 1897. Likewise, recovery was delayed after the Baring Crisis in Argentina in part because of decreased prices for agricultural exports, and renewed growth ultimately coincided with higher export prices. Increases in tariff rates also occurred during these recovery periods, though most consistently in the United States. However, the evidence suggests that higher commodity prices played more of a role in encouraging post-crisis economic growth than did trade policy changes in these countries over this period.
Keywords: 330; Crisis; recovery; tariffs; commodity prices; United States; Argentina